PENGEMBANGAN BAHAN AJAR BERBANTUAN AUGMENTED REALITY PADA MATA PELAJARAN INFORMATIKA ELEMEN SISTEM KOMPUTER FASE D DI KABUPATEN MAROS - Muhammad Alimka; Mustari Lamada; Hendra Jaya; Muhammad Ma’ruf Idris (UNM Journal of Technology and Vocational, 2024)
This research produces teaching materials assisted by Augmented Reality in Informatics subject of Phase D Computer System Elements in Maros regency which are valid, practical, and effective in improving learning outcomes. This type of research is R&D using the 4D development model, which includes: Define, Design, Develop, and Disseminate. The research subjects were grade VII students at UPTD SMPN 6 Moncongloe, UPTD SMPN 5 Mandai, and UPTD SMPN 16 Mandai. The subjects needed were 4 people for one to one trial and 12 people for small scale trial at UPTD SMPN 6 Moncongloe, 22 people for field trial at UPTD SMPN 16 Mandai, and validating testing of 55 people at UPTD SMPN 5 Mandai. The results of the research reveal that (1) the teaching materials are valid to be used based on the score from media expert which is 88.46 in Valid category and the material expert’s score is 90.05 in Valid category as well; (2) the teaching materials are practical to be used based on the score from teachers, which is 87.53 in Practical category, the score from students is 86.66 in Practical category, and the score from observer is 88.19 in Practical category, and (3) the N-Gain score from pre- test and post-test is 0.71 with High category, so it can be stated that this teaching material is effective in improving learning outcomes in Informatics subject of Phase D Computer System Elements.